Are Electronic Cardiac Devices Still Evolving? - Carrault, G.; Mabo, P. (Yearbook of Medical Informatics, 2014)
Objectives: The goal of this paper is to review some important issues occurring during the past year in Implantable devices.Methods: First cardiac implantable device was proposed to maintain an adequate heart rate, either because the heart’s natural pacemaker is not fast enough, or there is a block in the heart’s electrical conduction system. During the last forty years, pacemakers have evolved considerably and become programmable and allow to configure specific patient optimum pacing modes. Various technological aspects (electrodes, connectors, algorithms diagnosis, therapies, ...) have been progressed and cardiac implants address several clinical applications: management of arrhythmias, cardioversion / defibrillation and cardiac resynchronization therapy.Results: Observed progress was the miniaturization of device, increased longevity, coupled with efficient pacing functions, multisite pacing modes, leadless pacing and also a better recognition of supraventricular or ventricular tachycardia’s in order to deliver appropriate therapy. Subcutaneous implant, new modes of stimulation (leadless implant or ultrasound lead), quadripolar lead and new sensor or new algorithm for the hemodynamic management are introduced and briefly described. Each times, the main result occurring during the two past years are underlined and repositioned from the history, remaining limitations are also addressed.Conclusion: Some important technological improvements were described. Nevertheless, news trends for the future are also considered in a specific session such as the remote follow-up of the patient or the treatment of heart failure by neuromodulation.
Keywords: Implantable device; leadless sensor; management of hemodynamic; subcutaneous implantable device; quadripolar lead